Banking Roles and Policies in Anticipating Cyber Attacks in Indonesia (Jurnal Kepastian Hukum dan Keadilan, 2023)
Every year, Indonesia expands. The expansion of digital transformation is a milestone for all industries, including finance. In addition, cybercrime is believed to be on the rise and poses a threat to institutions and customers. And the banking system must also be responsible for safeguarding customer data, and cooperation with customers is expected to be more thorough when using data. Obviously, the digital revolution has contributed significantly to the advancement of both the banking and non-banking sectors. In this instance, however, the banking industry is primarily culpable for this cyber attack. In this paper, the researcher employs a qualitative descriptive method in order to facilitate the writer's analysis of a theory and current legal policies governing banking and cyber, which is a major concern for everyone if it is misused or if it is discovered that bankers are not careful in managing everything. customer data. This study's findings will analyze the role and policies of banks in relation to the transformation of the contemporary digital era. Then, it analyzes the cyber security system, which, as we all know, is not only the responsibility of the banking sector as a service provider, but also that of the customer, who must not be careless in providing banking-related confidential information so that it cannot be easily accessed by criminals. who intentionally intend to take benefits.Keywords: Banking, Cyber Attack, Cyber, Security System